e-Knowledge: an approach to fostering manufacturing know-how at the shop floor - Tjahjono, Benny; Bin, Wu (Production and Operations Management Society, 2001)
This paper presents an application of the web technology in promoting knowledge management at the shop floor, known as e-knowledge. The system is expected to promote sharing and reusing various levels of manufacturing information from assembly cell to testing area, and from documentation to training. The implementation of such a system has been made possible by utilising the web-programming environment. To investigate how the e-knowledge works, a case study involving a major cellular telecommunication industry is presented.